Effect of Surface Morphology on Dynamic Characteristics of Cam-Follower Oblique Impact System - Wangqun Deng; Haibo Feng; Jianjun Wang; Yongfeng Yang (Shock and Vibration)
The effects of the fractal characteristics on the dynamic characteristics of the oblique impact system are studied via considering the normal contact stiffness with fractal dimension parameter of the microstructure of the interface in this paper. The normal distribution is used to describe the trend of contact line length. The effects of the position parameters and the scale parameters are analyzed. The simulation results show that the increasing of the interface roughness can make the system response more stable. The system response eventually evolves into chaos as the fractal dimension increases. The system response changes between quasiperiod and chaos affected by the contact line length with a normal random distribution.